Neonatal clavicle fracture: A review of fourteen cases in East Coast Peninsular Malaysia - Awang, Mohd Shukrimi; Abdul Razak, Ardilla Hanim; Che Ahmad, Aminudin; Mohd Rus, Razman (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2017)
Introduction: The purpose of this study is to identify the incidence of clavicle fractures in newborn associated with fetal, maternal and process of deliveries in Kuantan General Hospital from June 2012 until January 2014. This study is to determine epidemiological data of clavicle fractures, maternal and baby risk factors associated with clavicle fractures of newborn and its’ outcome. Methods: This is a prospective study. 13 patients were identified to fulfill the inclusion criteria of the study. The data of sociodemographic, associated fetal and maternal risk factors and the outcomes were recorded using proforma. The statistical data analysis was done using SPSS 12.0. Results: Out of 20,257 live births at our centre during the study period, 13 infants were diagnosed to have clavicle fractures, giving an incidence of 0.64 per 1000 live births. There were 5 (38.5%) left, 7 (53.8%) right and one (7.7%) bilateral fracture. All fractures located at the mid shaft of the clavicle and none have associated brachial plexus injuries. All infants were delivered through vaginal delivery (61.5%); five through assisted delivery (instrumental); 2 (15.4%) forcep and 3 (23.1%) vacuum. Two of the babies developed shoulder dystocia. The average birth weight was 3371 grams (SD 0.269) and mean gestational age was 38.7 weeks (SD 1.16). Five of the mothers (38.5%) were primigravida and eight (61.5%) were multigravida in which,7 (53.8%)were healthy without other co-morbidty, 5 (38.5%) having gestational diabetis and one (7.7%) hypertension. The average maternal weight was 62.0 kg and height 1.58 metres with average BMI of 24.16 (3.29SD). All eventually had a complete recovery at 6 weeks with clinical and radiological evident of fracture union. Conclusions: In conclusion, all patients with clavicle fractures were found following vaginal delivery. There were no associations between neonatal clavicle fractures with maternal or baby risk factors. All fractures healed without any complications. KEYWORDS: Brachial plexus, shoulder dystocia, clavicle fractures